A sheet-like porous carbon for high-rate supercapacitors produced by the carbonization of an eggplant. (October 2015) - Li, Zhengjie; Lv, Wei; Zhang, Chen; Li, Baohua; Kang, Feiyu; Yang, Quan-Hong
Abstract: N-doped porous carbon sheets are produced by a one-step carbonization of a selected biomass precursor, eggplant. Such a carbon synergistically inherits sheet-like microstructure and naturally rich nitrogen in eggplant and shows excellent rate performance as a supercapacitor electrode due to the short ion diffusion paths.